2005
DOI: 10.1007/s10147-004-0457-6
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the bilharzial and non-bilharzial urinary bladder: a review of etiological features, natural history, and management

Abstract: Squamous cell carcinoma of the urinary bladder, though uncommon in Europe and the United States, is the most common variety of bladder tumor in countries where urinary bilharziasis prevails. A great controversy still exists regarding its natural history and management. Here, we review the literature of bilharzial and nonbilharzial squamous cell carcinoma of the urinary bladder, focusing on large series. Our aim was to gather most of the published data about this disease entity, report it in a systematic compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 57 publications
3
55
2
3
Order By: Relevance
“…Moreover, the diagnosis of schistosomiasis was not based strictly on diagnostic tools, e.g., presence of schistosomal ova or pathologic lesions in bladder tissue; past schistosomal infection as indicated by the patient medical record was sufficient for a positive schistosomiasis diagnosis in this study. Information on past history is liable to some bias as patients from rural Egypt may give a false negative history because of fear of receiving anti-bilharzial injections [42]. Therefore, estimates on schistosomal infection from our study are an underestimate and would conservatively bias ORs toward the null value.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, the diagnosis of schistosomiasis was not based strictly on diagnostic tools, e.g., presence of schistosomal ova or pathologic lesions in bladder tissue; past schistosomal infection as indicated by the patient medical record was sufficient for a positive schistosomiasis diagnosis in this study. Information on past history is liable to some bias as patients from rural Egypt may give a false negative history because of fear of receiving anti-bilharzial injections [42]. Therefore, estimates on schistosomal infection from our study are an underestimate and would conservatively bias ORs toward the null value.…”
Section: Discussionmentioning
confidence: 86%
“…At first diagnosis, patients presenting with SCC associated with schistosomal infection have locally advanced tumors and a mean age, that is, generally 10-20 years younger than that of patients with non-schistosomal bladder cancer, indicating the rapid development of this type, irrespective of the aging of the general population [42]. El-Bolkainy et al (1981) reported a significantly lower age at diagnosis in egg-positive bladder cancer patients compared to egg-negative cases in a pathology series consisting of radical cystectomy specimens [10].…”
Section: Discussionmentioning
confidence: 99%
“…Sistoskopide genellikle solid tümörler şeklinde gözlenir. Sık-lıkla tanı anında T3 veya T4 evresindedir ve lenf nodu tutulum oranları % 15-20'dir [10]. Tedavide en etkin yöntem radikal sistektomi ve adjuvan tedavilerdir.…”
Section: Olguunclassified
“…Bizim olgumuzda, tümöre eşlik eden sistitis glandülaris bulunmazken tümörün mesane tabanı ve yan duvarı tutması ve abdominal tomografi ve gastrointestinal sistem (GİS) endoskopisi sonuçlarının başka bir primer tümör odağını göstermemesi nedeniyle, primer mesane adenokarsinomu olarak kabul edilmiştir. Kemoterapi olarak 5-Florourasil, Doxorubisin ve Sisplatin kombinasyonunun kullanımı denenmektedir [10]. Sonuç olarak bu tümörlerde, her türlü tedaviye rağmen 5 yıllık yaşam beklentisi % 40'ın altındadır.…”
Section: Olguunclassified
“…8 Surgical intervention is the preferred management as there is currently a lack of evidence to support the efficacy of chemotherapy/radiotherapy in treating primary bladder SCC and tumour response to these treatment modalities is frequently suboptimal. 9 There are some small studies that have suggested there may be a benefit from neoadjuvant irradiation. 10 Approximately 25% of cases are too advanced for surgery at presentation.…”
mentioning
confidence: 99%